Continuous enterprise development in Java - Rubinger, Andrew Lee (O'Reilly, 2014)
Learn a use-case approach for developing Java enterprise applications in a continuously test-driven fashion. With this hands-on guide, authors and JBoss project leaders Andrew Lee Rubinger and Aslak Knutsen show you how to build high-level components, from persistent storage to the user interface, using the Arquillian testing platform and several other JBoss projects and tools. Through the course of the book, youu2019ll build a production-ready software conference tracker called GeekSeek, using source code from GitHub. Rubinger and Knutsen demonstrate why testing is the very foundation of developmentu2014essential for ensuring that code is consumable, complete, and correct. Bootstrap an elementary Java EE project from start to finish before diving into the full-example application, GeekSeek Use both relational and NoSQL storage models to build and test GeekSeeku2019s data persistence layers Tackle testable business logic development and asynchronous messaging with an SMTP service Expose enterprise services as a RESTful interface, using Java EEu2019s JAX-RS framework Implement OAuth authentication with JBossu2019s PicketLink identity management service Validate the UI by automating interaction in the browser and reading the rendered page Perform full-scale integration testing on the final deployable archive.